2021
DOI: 10.1186/s40814-021-00793-4
|View full text |Cite
|
Sign up to set email alerts
|

Qigong mind-body program for caregivers of cancer patients: design of a pilot three-arm randomized clinical trial

Abstract: Background Informal caregivers, often family and friends, experience significant psychological and physical distress leading to reductions in health and quality of life (QOL). Mind-body interventions focused on caregivers are often limited and do not address multiple barriers, including caregivers’ economic, geographic, and time constraints. Translation of in-person, community-based interventions to Internet-based delivery may offer greater accessibility for caregivers, leading to increased adh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…(2019)[ 31 ] and Shani et al . (2021),[ 16 ] who identified depression and anxiety as the most prevalent psychological symptoms in female caregivers. Another study reported an increased burden of care, decreased health, depression, and anxiety in female caregivers providing for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2019)[ 31 ] and Shani et al . (2021),[ 16 ] who identified depression and anxiety as the most prevalent psychological symptoms in female caregivers. Another study reported an increased burden of care, decreased health, depression, and anxiety in female caregivers providing for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results refer to chronic mental exhaustion in caregivers, which may predispose them to depression. [ 16 ] Oechsle et al . (2019)[ 13 ] also reported high levels of mental exhaustion in female caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most community-living older adults, families often are the primary source of care and support, contributing services that would cost enormous monetary expenses annually if they had to be purchased ( Hazzan et al, 2022 ; Langa et al, 2001 ). Caregivers are considered essential national healthcare resources ( Cheng et al, 2020 ; Schulz & Sherwood, 2008 ), and their quality of life is related to the quality of care and quality of life of the care recipients ( Shani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…cognitive impairment [34], hypertension [35], and cancer [36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%